Orofasial Clock: A Guide Principles in Treatment Planning - Wan Abdul Fattah Wan Ismail; Nalisha Mohamed Ramli; Mualimin Mochammad Sahid; Nik Salida Suhaila Nik Saleh; Haslinda Ramli; Nor Azura Ahmad Tarmidzi; Nadia Halib; Shofian Bin Ahmad; Nur Akilah Binti Abdul Ghaffar (Fakulti Pengajian Kotemporari Islam, UNISZA, 2024)
Al-Quran and Hadith is the paramount reference for problems solving, regardless of the place, condition and time range. Texts of the Qur'an and Sunnah mostly are of general in nature to facilitate its application in the general principles and substitute issues of laws. These general principles will ease the legal fiqh consideration in the clinical management of Orofacial Cleft. Orofacial Cleft is craniofacial birth defects involving every 700 - 1000 live births. The aim of this study is to evaluate the current fatwas in the treatment of Orofacial Cleft and discuss the principles of fiqh related to Orofacial Cleft that can be used as guidance for the medical and dental practitioners. Information regarding these issues is gathered through the study of fatwas, books of fiqh and medicine as well as reference to scholars of fiqh and Orofacial Cleft. As a conclussion, the principles of fiqh including Al-Darurat Tubihu al-Mahzurat, Al-Darurat Tuqaddaru Biqadariha and Al-Umur Bimaqasidiha are applicable as guideline in the treatment of Orofacial Cleft.